Legalisasi QR-Code sebagai Validasi dan Pengganti Tanda Tangan Pada Salinan Akta Notaris - Fitra Deni; Irnanda, Firli (Universitas Semarang, 2026)
This study aims to examine the legality of using QR-Codes as a validation mechanism and a substitute for signatures on copies of notarial deeds within the Indonesian legal system and to formulate directions for regulatory reform. The research is motivated by the increasing risk of forgery of notarial deed copies and the limitations of the Notary Law (UUJN), which has not explicitly accommodated electronic authentication mechanisms, despite the recognition of electronic signatures under the Electronic Information and Transactions Law (UU ITE). This research employs a normative juridical method using statutory, conceptual, comparative, and philosophical-progressive approaches. The findings indicate that under the current legal framework (lex lata), QR-Codes cannot yet be fully recognized as a substitute for notarial signatures on deed copies. However, normatively and conceptually, QR-Codes possess strong potential to be legalized as an electronic authentication mechanism, provided that they are synchronized with the UU ITE and supported by an official state verification system. The novelty of this study lies in proposing a normative synchronization model between the UUJN and the UU ITE that positions QR-Codes as a form of electronic validation, as well as in formulating a regulatory blueprint for QR-Code-based verification of notarial deed copies integrated with the AHU Online system. This study recommends regulatory reform in notarial law to enhance legal certainty, prevent document forgery, and improve efficiency and public trust in notarial practices in the digital era. Penelitian ini bertujuan menganalisis legalitas penggunaan QR-Code sebagai validasi dan pengganti tanda tangan pada salinan akta notaris dalam sistem hukum Indonesia serta merumuskan arah pembaruan pengaturannya. Penelitian ini dilatarbelakangi oleh meningkatnya risiko pemalsuan salinan akta notaris dan keterbatasan Undang-Undang Jabatan Notaris (UUJN) yang belum secara eksplisit mengakomodasi mekanisme autentikasi elektronik, meskipun Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) telah mengakui keabsahan tanda tangan elektronik. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan peraturan perundang-undangan, konseptual, komparatif, dan filosofis-progresif. Hasil penelitian menunjukkan bahwa secara hukum positif (lex lata), QR-Code belum dapat diposisikan sepenuhnya sebagai pengganti tanda tangan notaris pada salinan akta, namun secara normatif dan konseptual memiliki potensi kuat untuk dilegalkan sebagai mekanisme autentikasi elektronik sepanjang disinkronkan dengan ketentuan UU ITE dan didukung oleh sistem verifikasi resmi negara. Kebaruan penelitian ini terletak pada perumusan model sinkronisasi norma antara UUJN dan UU ITE yang menempatkan QR-Code sebagai instrumen validasi elektronik, serta penyusunan blueprint regulasi verifikasi salinan akta notaris berbasis QR-Code yang terintegrasi dengan sistem AHU Online. Penelitian ini merekomendasikan pembaruan regulasi kenotariatan guna memperkuat kepastian hukum, mencegah pemalsuan dokumen, dan meningkatkan efisiensi serta kepercayaan publik terhadap praktik kenotariatan di era digital.